(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
The landscape of English teaching has undergone remarkable transformations in recent years, reflecting the growing need for adaptable, learner-centric, and technologically driven approaches. This article delves into modern methods of English instruction, including communicative language teaching, task-based learning, and digital pedagogy, while also touching on the evolution of flipped classrooms and gamification. By exploring theoretical foundations, practical applications, and real-world challenges, the article seeks to provide a holistic understanding of how these methods shape language learning today.